Analysis of exchange rate movements: a case study of Singapore - Chia, Ailsan (2014)
This study focuses on movements in the US$/Singapore$ exchange rate. In order to understand movements in this nominal bilateral rate, the real and PPP rates are estimated and explained closely. The Singapore dollar is tightly managed and the role of the MAS is discussed in detail. The study examines the relationships between the current account, capital account and exchange rate trends. Monetary models suddest that relative infalition rates, interest rates, GDP growth rates and money supply growth rates determine exchange rate movements. The extent to which these factors affect the Singapore dollar is assessed. The study also present an ARIMA model for use in short-term forecasting.